Application of anatomic reconstruction technique for periurethral structure in robotic assisted laparoscopic radical prostatectomy - Li, Haichang; Lu, Dongning; Hu, Yuning; Mou, Yixuan; Zhang, Dahong; Liu, Zhenghong (Frontiers in Oncology, 2023)
Objective To investigate the outcome of patients underwent anatomic periurethral reconstruction during robotic assisted laparoscopic radical prostatectomy (RARP). Materials and methods During August 2016 to May 2018, periurethral structure anatomic reconstruction was performed during RARP in 58 consecutive patients. The control group consists of another 50 patients had no reconstruction procedure during RARP. Perioperative data of these patients were collected retrospectively, including operation time, anastomosis time, intraoperative blood loss, duration of indwelling catheter, length of hospital stay, complications, postoperative pathology, and continence outcome at 1,3,6 and 12 months. Results All cases were successfully performed without conversion to open or laparoscopic surgery. There were no major intraoperative or postoperative complications.The percentage of patients maintain continence in the reconstruction group versus non-reconstruction group: At 1 month 84.5% (49/58)versus 70.0% (35/50), at 3 months 89.7% (52/58)versus 78.0% (39/50), at 6 months 91.3% (53/58)versus 86.0% (43/50) and 1 year after surgery 100.0% (58/58)versus 96.0% (48/50). Reconstruction group showed better continence outcome in 1 and 3 months (P<0.05). There is no statistical differences in 6 month and 1 year. Conclusion Anatomic reconstruction of periurethral structure during RARP is safe and feasible with reduced duration of indwelling catheter and better continence outcome.